2023
DOI: 10.1007/s12035-023-03519-0
|View full text |Cite|
|
Sign up to set email alerts
|

The States of Different 5-HT Receptors Located in the Dorsal Raphe Nucleus Are Crucial for Regulating the Awakening During General Anesthesia

Abstract: General anesthesia is widely used in various clinical practices due to its ability to cause loss of consciousness. However, the exact mechanism of anesthesia-induced unconsciousness remains unclear.It is generally thought that arousal-related brain nuclei are involved. 5-hydroxytryptamine (5-HT) is closely associated with sleep arousal. Here, we explore the role of the 5-HT system in anesthetic awakening through pharmacological interventions and optogenetic techniques. Our data showed that exogenous administra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Building on our preliminary findings 15,35 , which illustrate the involvement of the DR-BLA 5-HTergic neural circuit in regulating recovery from sevoflurane anesthesia, we hypothesize that the CeA and mPFC may represent secondary and tertiary projection nuclei in this 5-HTergic circuit. The upstream DRN is speculated to regulate this extensive 5-HTergic projection circuit, collectively modulating arousal from sevoflurane anesthesia.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Building on our preliminary findings 15,35 , which illustrate the involvement of the DR-BLA 5-HTergic neural circuit in regulating recovery from sevoflurane anesthesia, we hypothesize that the CeA and mPFC may represent secondary and tertiary projection nuclei in this 5-HTergic circuit. The upstream DRN is speculated to regulate this extensive 5-HTergic projection circuit, collectively modulating arousal from sevoflurane anesthesia.…”
Section: Discussionmentioning
confidence: 71%
“…Our recent series of studies indicate that activating DR 5-HT neurons and their projections to the BLA can effectively reduce the recovery time from sevoflurane anesthesia. Importantly, different 5-HT autoreceptors within the DR may play significant roles in facilitating anesthesia arousal, particularly as both presynaptic 5-HT1A autoreceptors in the DR and postsynaptic 5-HT1A receptors in the BLA exhibit similar arousal-promoting effects 36,37 . Therefore, in this study, we aim to further investigate the neural circuits associated with consciousness alterations under sevoflurane anesthesia and the 5-HTergic system, building upon these findings.…”
Section: Discussionmentioning
confidence: 99%
“…The LHb can directly project to the DRN or indirectly innervate the DRN through GABAergic neurons of RMTg [ 37 ], with indirect innervation playing a dominant role. Based on previous research into the involvement of the DRN in the recovery from general anesthesia [ 28 , 39 , 40 ], we speculate that the LHb may indirectly modulate the function of the DRN in ciprofol anesthesia via the GABAergic neurons of RMTg.…”
Section: Discussionmentioning
confidence: 95%
“…The expression of both 5-HT1AR and 5-HT2AR was decreased in the SCh and LC but increased in the RN and POA. A study showed that 5-HT1AR in the RN and reticular formation is involved in rapid eye movement (REM) sleep [ 44 , 45 ], and both 5-HT1AR and 5-HT2AR are essential for general anaesthesia awakening [ 46 ]. The hypothalamic preoptic area is associated with thermoregulation and sleep [ 47 ].…”
Section: Discussionmentioning
confidence: 99%